T025 Optimizing logical coupling between brain stimulation and pharmacotherapy with use of animal models. Issue 3 (March 2017) - Rotenberg, A.
Abstract : Adaptations of noninvasive brain stimulation protocols to animal models offers opportunities for insight into the molecular and cellular consequences of techniques such as rTMS and tDCS. Beyond identifying mechanisms by which these and related protocols alter brain function, in vivo and in vitro translational experiments can uncover signalling pathways that are both engaged by noninvasive brain stimulation and also contain therapeutic drug targets. Thus paired drug-device combinations may be tested in preclinical experiments where relatively high-throughput systematic manipulation of stimulation parameters and drug choice and dose is much more practical than in clinical studies. Accordingly this presentation summarizes experiments aimed to address practical gaps in knowledge that may be encountered in the clinical arena, where in many disease states a patient is unlikely to undergo stimulation without concomitant drug treatment, and where the therapeutic efficacy of noninvasive brain stimulation may be incomplete and can be improved by selective drug treatment.